Endothelin‐1 increases CHSY‐1 expression in aortic endothelial cells via transactivation of transforming growth factor β type I receptor induced by type B receptor endothelin‐1. (27th February 2019) - Seif, Faezeh; Little, Peter J.; Niayesh‐Mehr, Reyhaneh; Zamanpour, Masoumeh; Babaahmadi‐Rezaei, Hossein
Abstract: Objectives: TGF‐β through hyperelongation of glycosaminoglycan (GAG) chains leads to binding of low‐density lipoproteins to the proteoglycans. The vasoactive peptide, endothelin‐1 (ET‐1), plays a key role in the development of atherosclerosis. This study addressed the question whether ET‐1 by activating the Rho kinase and cytoskeletal rearrangement can transactivate the TGF‐β receptor leading to phosphorylation of the transcription factor Smad2 and increased expression of the GAG chain synthesizing enzyme such as chondroitin synthase‐1 (CHSY‐1) in bovine aortic endothelial cells (BAECs). Methods: In this study, intermediates in ET‐1‐induced Smad2C phosphorylation and the protein level of CHSY‐1 were identified and quantified by Western blotting. Key findings: Endothelin‐1 caused time‐dependent phosphorylation of Smad2C which was inhibited in the presence of the endothelin B receptor antagonist, BQ788. The response to ET‐1 was inhibited by the Rho/ROCK kinase antagonist, Y27632 and by cytochalasin D, an inhibitor of actin polymerization but the ET‐1‐mediated pSmad2C was not inhibited by the matrix metalloproteinase (MMP) inhibitor, GM6001. ET‐1 increased CHSY‐1 protein level, which was inhibited in the presence of BQ788, cytochalasin D and Y27632. Conclusions: Endothelin‐1 signalling via the ETB receptor utilizes cytoskeletal rearrangement and Rho kinase but not MMPs leading to TβRI transactivation signalling and phosphorylation of Smad2C and through this pathway increased the level of CHSY‐1.